Membangun Kesadaran Mahasiswa tentang Pentingnya Pendidikan Kewarganegaraan di Era Digital Program Studi PGSD - Suyono Suyono; Dionisius Ronaldino Fernandes Dugis; Tarizkya Nianwardani; M. Imam Maliki; Putri Nabilla Mujo Widyaharum; Shisi Raisyah Everdiana; Shecyl Ananda Agusta Putri (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Civic Education has a role in shaping the character and social awareness of students, especially in the digital era which is full of challenges due to the development of information and communication technology. Students are not only required to understand civic values but also implement them both in real life and in the digital space. This research aims to build awareness of PGSD Study Program students about the importance of civic education in the digital era and examine how interactive approaches and the use of digital media can increase students' active participation in social, political, and cultural issues. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and literature studies. The subject of the study is PGSD students who take the Civic Education course. The results of the study show that the application of learning strategies that utilize digital technology can increase students' understanding and awareness of their role as citizens. Students become more reflective and critical of civic issues and motivated to be involved in social actions. Civic education that is contextual and adaptive to the development of the times is important in shaping a responsible and characterful digital generation.